Increased rate of complications in myasthenia gravis patients following hip and knee arthroplasty: a nationwide database study in the PearlDiver Database on 257,707 patients - Sherman, William F; Wu, Victor J; Ofa, Sione A; Ross, Bailey J; Savage-Elliott, Ian D; Sanchez, Fernando L (Acta Orthopaedica, 2021)
Background and purpose — The increasing prevalence of total hip arthroplasty (THA) and total knee arthroplasty (TKA) within the growing elderly population is translating into a larger number of patients with neuromuscular conditions such as myasthenia gravis (MG) receiving arthroplasty. We compared systemic and joint complications following a THA or TKA between patients with MG and patients without MG. Patients and methods — Patient records were queried from PearlDiver (Pearl Diver Inc, Fort Wayne, IN, USA), an administrative claims database, using ICD-9/ICD-10 and Current Procedural Terminology codes. In-hospital and 90-day post-discharge rates of systemic and joint complications were compared between the 2 cohorts. Results — 372 patients with MG and 249,428 patients without MG who received a THA or TKA were included in the study. At 90 days post-discharge, MG patients exhibited exhibited between 1.6 and 15% higher rates of systemic complications, including cerebrovascular event, pneumonia, respiratory failure, sepsis, myocardial infarction, acute renal failure, anemia, and deep vein thrombosis (all p < 0.001). The same results were also found during the in-hospital time period. 90-day incidence of aseptic loosening was the only joint complication with significantly increased odds risk for the MG cohort (OR 5; 95% CI 2–12). Interpretation — Patients with MG exhibited significantly higher risk for multiple systemic complications during the index hospital stay and in the acute post-discharge setting.